Structural assessment of SARS-CoV2 accessory protein ORF7a predicts LFA-1 and Mac-1 binding potential. Issue 1 (29th January 2021) - Nizamudeen, Zubair Ahmed; Xu, Emma-Ruoqi; Karthik, Vivin; Halawa, Mohamed; Arkill, Kenton P.; Jackson, Andrew M.; Bates, David O.; Emsley, Jonas
Abstract: ORF7a is an accessory protein common to SARS-CoV1 and the recently discovered SARS-CoV2, which is causing the COVID-19 pandemic. The ORF7a protein has a structural homology with ICAM-1 which binds to the T lymphocyte integrin receptor LFA-1. As COVID-19 has a strong immune component as part of the disease, we sought to determine whether SARS-CoV2 would have a similar structural interaction with LFA-1. Using molecular docking simulations, we found that SARS-CoV2 ORF7a has the key structural determinants required to bind LFA-1 but also the related leukocyte integrin Mac-1, which is also known to be expressed by macrophages. Our study shows that SARS-CoV2 ORF7a protein has a conserved Ig immunoglobulin-like fold containing an integrin binding site that provides a mechanistic hypothesis for SARS-CoV2's interaction with the human immune system. This suggests that experimental investigation of ORF7a-mediated effects on immune cells such as T lymphocytes and macrophages (leukocytes) could help understand the disease further and develop effective treatments.